2007
DOI: 10.1016/j.cellbi.2007.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibitory actions of prothrombin on normal hepatocytes: Influence of matrix

Abstract: Most hepatomas have a defect in prothrombin carboxylation, and can secrete under-carboxylated prothrombin or des-γ-carboxy-prothrombin (DCP), the function of which is unknown. We considered that prothrombin-DCP axis might also be involved in growth control. Hepatocytes and hepatoma cells were treated with prothrombin, and DNA synthesis and cytoskeleton were studied. Prothrombin inhibited DNA synthesis in hepatocytes on fibronectin, but not collagen matrix. Hepatoma cell lines were not inhibited. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…Since K vitamins have been shown to have growth inhibitory activities (Wang et al, 1995; Nishikawa et al, 1995; Hitomi et al, 2005) and prothrombin is a major vitamin K dependent blood coagulation factor, we hypothesized that prothrombin might also be a cell growth regulator. Our previous investigation showed that prothrombin significantly inhibited normal hepatocyte DNA synthesis in fibronectin‐coated culture dishes, confirming that prothrombin is a cell growth inhibitor and this growth inhibitory effect is mediated by cell–matrix interactions (Carr et al, 2007).…”
mentioning
confidence: 61%
See 3 more Smart Citations
“…Since K vitamins have been shown to have growth inhibitory activities (Wang et al, 1995; Nishikawa et al, 1995; Hitomi et al, 2005) and prothrombin is a major vitamin K dependent blood coagulation factor, we hypothesized that prothrombin might also be a cell growth regulator. Our previous investigation showed that prothrombin significantly inhibited normal hepatocyte DNA synthesis in fibronectin‐coated culture dishes, confirming that prothrombin is a cell growth inhibitor and this growth inhibitory effect is mediated by cell–matrix interactions (Carr et al, 2007).…”
mentioning
confidence: 61%
“…Since our previous data showed that PT inhibits hepatocyte DNA synthesis on fibronectin matrix, and causes fibronectin degradation (Carr et al, 2007), we reasoned that the effects of prothrombin on DNA synthesis inhibition might be related to fibronectiin receptor integrin α5 signaling. We first examined the integrin α5 phosphorylation status.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Abnormally prolonged prothrombin time, an indication of reduced coagulation function, has been discovered to be associated with aggravated stage in cases of gastric and lung cancer [58], [59]. Moreover, data of [60] supported that prothrombin is involved in cell cycle regulation as a DNA synthesis inhibitor, possibly through an induction of cytoskeleton deorganization. This inhibition was only observed in hepatocytes but not in hepatoma cells likely due to different extracellular matrix (ECM) protein interactions in normal versus cancer condition.…”
Section: Resultsmentioning
confidence: 99%